MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN KESADARAN EKOLOGI DI SMA MODEL NEGERI 3 PALU SULAWESI TENGAH - Iskandar; Hamlan Andi Baso Malla (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
Head of SMA Negeri 3 Palu implements the form of management based on five management functions, namely planning, organizing, staffing (placement), coordinating and controlling (control). In managing ecology-oriented schools refers to the school adiwiyata ie schools that maintain the environment, the arrangement of a clean environment, beautiful and healthy in order to produce a good learning environment. this effort also aims to provide understanding of the school community in the preservation of environmental functions and resources in the school environment. Environmentally sound environmental (ecological) school programs have participatory and sustainable principles. The participatory principle is that the school community involved in school management covers the whole process of planning, implementation, and evaluation based on responsibility. The principle of sustainability is that all activities are carried out comprehensively, planned and continuously in improving the learning conditions more comfortable and conducive for all citizens of the school.